Hard measures for soft stuff: citizenship indicators and educational policy under the Lisbon Strategy - Holford, John (Symposiun Journals, 2008)
How far is the European Union a vehicle for inclusion and empowerment of a new range of policy actors in education? This article explores the role of actors in policy formation through a case study. It examines European Union attempts since 2000 to develop indicators of ‘active citizenship’ and ‘education and training for active citizenship’. It is based on two main sources: policy documents on the development of indicators and benchmarks; and a case study of an exercise (2005-07) to develop such indicators, initiated by the European Commission’s Directorate General for Education and Culture. It shows that policy actors have attempted to take advantage of the Open Method of Coordination, often seen as a neo-liberal control mechanism, to ensure that citizenship remains on the policy agenda.